The commitment of the European Union to no longer be vulnerable to gas supply from Russia - Cornelia NEAGU; Marius BULEARCĂ; Cristian SIMA; Daniel FISTUNG (Communications of International Proceedings, 2023)
Exposing the EU to volatile energy market prices is perceived as the highest risk for the future before the transition to renewable energy brings the desired market stability. Hence, taking into account the condition induced by the electricity and gas price rise worldwide, and the impact caused, it is necessary to institute temporary measures thereby electricity and gas prices end-users had to pay do not worsen the level of energy poverty. For these reasons, in the beginning the article presents a set of measures adopted both at the EU level and by some member states to reduce dependence on natural gas imports from Russia and to lower gas (and electricity) bills. Finally, the article extensively examines the measures to reduce the negative effects induced by the increase in gas prices in Romania. It is concluded that the further implementation of this strategy must allow Romania to use its high potential compared to other European countries, (mainly its own natural gas resouces), to become energy independent.
Keywords: natural gas; European Union; energy prices; compensations; correction mechanisms